STRATEGI CONTEXTUAL TEACHING LEARNING(CTL)PADA MATA PELAJARAN FIQIH DALAM MENANAMKAN SIKAP DISIPLIN DAN TANGGUNG JAWAB BERIBADAH SISWA KELAS IV MADRASAH IBTIDAIYAH RAUDLATUL MUTA’ALLIMIN BRINGIN KABUPATEN SEMARANG - Muhamad Rois; Rifqi Aulia Erlangga (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
The CTL strategy is an interesting phenomenon to study and research, considering that this CTL has a positive effect on learning outcomes, the objectives are: 1) Knowing the CTL, 2) Knowing the implementation of the CTL, 3) Knowing the supporting and inhibiting factors of the CTL. The research method used is naturalistic field research. The data in this study were obtained through observation, interviews and documentation. The results of this study indicate that the CTL for steps to instill discipline and responsibility. Second, the implementation of the CTL for Fiqh subjects in instilling discipline and responsibility for worship is guided by the seven components of the CTL. These components include: constructivism, inquiry, asking, learning community, modeling, reflection, and authentic assessment. Third, there are supporting and inhibiting factors in the implementation of the CTL for worship. Supporting factors include: teacher readiness, infrastructure, student activity, and learning environment. As for the inhibiting factors include: limited time, student abilities, and unequal supervision between the school environment and the family. The implication of the results of this research is that teachers can use CTL as a teaching method so that PBM or the teaching and learning process becomes more interesting to carry out studies and research for the sake of advancing education in the future.